2019
DOI: 10.1158/1078-0432.ccr-18-0841
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Tissue-Specific DNA Methylation Signatures for Thyroid Nodule Diagnostics

Abstract: Thyroid cancer is frequently difficult to diagnose due to an overlap of cytologic features between malignant and benign nodules. This overlap leads to unnecessary removal of the thyroid in patients without cancer. While providing some improvement over cytopathologic diagnostics, molecular methods frequently fail to provide a correct diagnosis for thyroid nodules. These approaches are based on the difference between cancer and adjacent thyroid tissue and assume that adjacent tissues are the same as benign nodul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…The reduced Δβ value combined with the small sample size probably accounted for the lack of significance of the FTA-NT comparison ( Supplementary Table 1). Similarly, Yim et al (2019) also noted that benign thyroid nodules frequently feature an epigenetic pattern intermediate between normal thyroids and malignant nodules.…”
Section: Dna Methylation Profiles Of Follicular Thyroid Neoplasmsmentioning
confidence: 80%
See 1 more Smart Citation
“…The reduced Δβ value combined with the small sample size probably accounted for the lack of significance of the FTA-NT comparison ( Supplementary Table 1). Similarly, Yim et al (2019) also noted that benign thyroid nodules frequently feature an epigenetic pattern intermediate between normal thyroids and malignant nodules.…”
Section: Dna Methylation Profiles Of Follicular Thyroid Neoplasmsmentioning
confidence: 80%
“…Importantly, the same study also suggested prognostic implications of the DNA methylation profile, with massive hypomethylation in aggressive (PDTC/ATC) thyroid cancer subtypes (Bisarro Dos Reis et al 2017). Recently, Yim et al (2019) showed that a DNA methylation-based molecular method, named Diagnostic DNA Methylation Signature approach (DDMS), features high sensitivity/specificity in the identification of malignant and benign thyroid nodules.…”
Section: Introductionmentioning
confidence: 89%
“…These findings, which are consistent with results from Mancikova et al andAffinito et al (Mancikova et al 2014, Affinito et al 2019), suggested that DNA methylation in promoters does not have a widespread role in controlling gene expression in PTC. On the other hand, by using RRBS, Yim et al identified a unique DNA methylation signature of 4,575 CpGs specific to benign nodules, most of which were hypermethylated compared to adjacent normal tissues and malignant nodules, that may have important diagnostic applications (Yim et al 2019).They also analyzed specimens with lymphocytic thyroiditis and, in accordance with the results from Bisarro dos Reis et al, suggested that the presence of immune-infiltrating cells in tumors may affect DNA methylation patterns (Bisarro dos .…”
Section: Epigenetic Alterationsmentioning
confidence: 99%
“…However, the series of samples used contained a low number of recurrent cases; thus, further analyses are required to validate its potential for prognostic use. Finally, Yim et al, who profiled PTC DNA methylation by RRBS, developed a new diagnostic method, the so-called diagnostic DNA methylation signature (DDMS) approach, which is based on 373 differentially methylated regions with tissue-specific DNA methylation patterns in benign and malignant nodules (Yim et al 2019). A notable proportion of these markers were associated with active enhancers and cancer-related genes.…”
Section: Focal Dna Methylation Alterations In Thyroid Cancer: Genome-mentioning
confidence: 99%
“…With these therapeutic approaches, most patients with PTC have a good prognosis, but there were some challenges for both patients and clinicians. The consequence of surgical excision that is one of the important treatments for thyroid cancer may be the increased incidence of hypothyroidism [5]; PTC is often difficult to diagnose because of similarities between malignant and benign nodules, which results in some benign patients having their thyroid removed [6]; treatment of refractory radioiodine differentiated thyroid cancer still faces challenges and some slowmoving tumors were overdiagnosed and overtreated. In terms of molecular therapy, the combined use of immune checkpoint inhibitors and BRAF (especially BRAFV600E) inhibitors is aussichtsreich in the treatment of thyroid cancer and some progress has been made [7].…”
mentioning
confidence: 99%